The Anti-Inflammatory Cytokine, Interleukin-10, Inhibits Inflammatory Mediators in Human Epithelial Cells and Mouse Macrophages Exposed to Live and UV-Inactivated Chlamydia trachomatis - Abebayehu N. Yilma; Shree R. Singh; Stacie J. Fairley; Murtada A. Taha; Vida A. Dennis (Mediators of Inflammation)
Chlamydia trachomatis infects macrophages and epithelial cells evoking acute and chronic inflammatory conditions, which, if not controlled, may put patients at risk for major health issues such as pelvic inflammatory disease, chronic abdominal pain, and infertility. Here we hypothesized that IL-10, with anti-inflammatory properties, will inhibit inflammatory mediators that are produced by innate immune cells exposed to C. trachomatis. We used human epithelial (HeLa) cells and mouse J774 macrophages as target cells along with live and UV-inactivated C. trachomatis mouse pneumonitis (MoPn) as stimulants. Confocal microscopy employing an anti-Chlamydia antibody confirmed cells infectivity by day 1, which persisted up to day 3. Kinetics studies revealed that live C. trachomatis induced TNF, IL-6, and IL-8, as a function of time, with day-2 infection inducing the highest cytokine levels. Exogenous IL-10 inhibited TNF, IL-6, and IL-8 as secreted by day-2 infected cells. Similarly, IL-10 diminished cytokine levels as produced by macrophages exposed to UV-inactivated Chlamydia, suggesting the IL-10-mediated inhibition of cytokines is not restricted to live organisms. Our data imply that IL-10 is an important regulator of the initial inflammatory response to C. trachomatis infection and that further investigations be made into IL-10 use to combat inflammation induced by this bacterium.